X-Ray Diffraction Contrast Tomography for Probing Hydrogen Embrittlement in Heat-Treated Lean Duplex Stainless Steel - Eguchi, Kenichiro; Burnett, Timothy L.; Engelberg, Dirk L. (Frontiers in Materials, 2022)
Laboratory-based diffraction contrast tomography (DCT) was applied to heat-treated lean duplex stainless steel (DSS) to observe microstructural changes by hydrogen infusion treatment. The feasibility of the DCT technique for the in-situ assessment of dual phase material with exposure to aqueous solution was investigated, with DCT observations carried out before and after cathodic hydrogen charging. The movement of diffraction spots was observed after charging for 7 days, which cannot be explained by sample lateral movements. An experimental method to apply DCT techniques for investigating hydrogen microstructure interaction is introduced here, but a more accurate experimental methodology is required to verify that the movement of diffraction spot derives from lattice parameter changes.